Pesquisa-ação com delegados de ensino sobre sexualidade, DST AIDS e drogas: um projeto pioneiro do interior do Estado de São Paulo - Bueno, Sônia Maria Virella (Brazilian Journal of Sexually Transmitted Diseases, 1997)
The opnions about sexuality, STD/AIDS and drugs of the education agents responsible for 1° and 2° grade schools were investigated. These re\lealed that problems have increased considerably; that the professors, who work whith these subjects, emphasises only the biologic aspect, not /inking the totality of theme, and the presence of HIV+ subjects and drug abusers. These evidenced the complexity of solutions for the problems, but they under stand that school is the apropriate local to work these knowledge, specific habilited, reaching the comportamental changes, with partnership with family, community, state, and the multidisciplinality, in the planning, execution and estimation of prevention actions in whole health of individual and collective.